Electrochemical performance of multi walled carbon nanotube and graphene composite films using electrophoretic deposition technique - Talib, Elyas; Lau, Kok Tee; Zainal Abidin, Muhammad Zaimi; Bistamam, Mohd Shahril Amin; Abdul Manaf, Nor Syafira; Raja Seman, Raja Noor Amalina; Zulkapli, Nor Najihah; Mohd Abid, Mohd Asyadi 'Azam (Trans Tech Publications, 2015)
This study aims to investigate multi-walled carbon nanotube and graphene composite thin films fabricated using cathodic electrophoretic deposition in aqueous solution. The deposition mechanism and films microstructure were investigated using the cyclic voltammetry (CV) and field emission scanning electron microscope. The depositions yield varied by the deposition time and deposition voltage. The composite films were studied for its application in the electrochemical capacitor. The electrochemical performance showed the capacitive behavior of the films in 6 M potassium hydroxide electrolyte. CV scans were verified from 0 to 1 V at different scan rates. The specific capacitance of 29 Fg-1 was achieved at the scan rate of 1 mVs-1.